Evaluation Of Design Change Risks On Time And Quality Control In Apartment Projects In Samarinda City - Hutagaol, Kerlima; Samosir, Maret Jerman; Sihite, Boy; E, Meliana Nur (Universitas Dharmawangsa Medan, 2026)
Design change is a common risk in construction projects and can significantly impact the efficiency of time control and work quality. This study aims to evaluate the impact of design change risk on time and quality control in a flat construction project in Samarinda. The research method used is a case study with a quantitative and qualitative descriptive approach, through interviews with the project team and analysis of project documents such as shop drawings, implementation schedules, and work progress reports. The results show that design changes that occurred in structural and architectural work caused a delay of 32 days from the initial schedule (from 365 days to 397 days). In addition, a decrease in quality efficiency was found due to revisions to working drawings and adjustments to technical specifications in the field. This impact can be minimized through the implementation of more intensive design coordination between planning consultants, supervisors, and contractors before work begins. This study emphasizes the importance of implementing design change risk management to maintain time control and quality in construction projects.